2021
DOI: 10.1016/j.xjon.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement in sheep with a novel trileaflet mechanical heart valve prosthesis without anticoagulation

Abstract: Background: Even after decades of intensive research, an ideal heart valve prosthesis remains elusive. Shortcomings of conventional devices include reduced durability of bioprostheses and the thrombogenicity of mechanical substitutes, necessitating anticoagulation and resulting in imperfect hemodynamics. Here we present in vivo results of a novel mechanical heart valve prosthesis aiming for freedom from anticoagulation.Methods: Four female sheep had their aortic valves replaced using the novel mechanical heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The importance of the straight cylindrical position of the commissures was recently reported by Paulsen et al ( 6 ), which highlighted that it results in preserved leaflet coaptation, decreased regurgitation and lower forces on the leaflets, potentially improving durability in contrast to Valsalva grafts (Vascutek Terumo, Vascutek Deutschland GmbH, Hamburg, Germany) with radially displaced commissures ( 6 ). These results once again confirm the paradigm that nature provides the best solution for any task, a concept that in my experience was also beneficial for other procedures: the bicaval heart transplantation ( 7 ), the direct anatomical anastomoses of the great arteries during correction of the transposition of the great arteries ( 8 ), the subcoronary Ross operation and even a novel anticoagulation-free mechanical heart valve with three wing-shaped leaflets ( 9 ). But not only an anatomically correct prosthesis, but also adequate surgery is decisive for success, and the David procedure is challenging.…”
Section: Discussionsupporting
confidence: 68%
“…The importance of the straight cylindrical position of the commissures was recently reported by Paulsen et al ( 6 ), which highlighted that it results in preserved leaflet coaptation, decreased regurgitation and lower forces on the leaflets, potentially improving durability in contrast to Valsalva grafts (Vascutek Terumo, Vascutek Deutschland GmbH, Hamburg, Germany) with radially displaced commissures ( 6 ). These results once again confirm the paradigm that nature provides the best solution for any task, a concept that in my experience was also beneficial for other procedures: the bicaval heart transplantation ( 7 ), the direct anatomical anastomoses of the great arteries during correction of the transposition of the great arteries ( 8 ), the subcoronary Ross operation and even a novel anticoagulation-free mechanical heart valve with three wing-shaped leaflets ( 9 ). But not only an anatomically correct prosthesis, but also adequate surgery is decisive for success, and the David procedure is challenging.…”
Section: Discussionsupporting
confidence: 68%
“…An alternative, although more expensive, might be ex vivo modelling [31]. Such a methodology was applied in the study of a novel trilea et valve [15,32]. The authors mounted the valve in a pulse duplicator that simulated the physiological system and studied, among others, clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the TRI valve better conserved the helical ow than the BIL valve. Schaller et al [15] implanted four novel mechanical prostheses of the aortic valve in sheep. The mechanical valves consisted of three lea ets made of poly-ether-ether-ketone.…”
Section: Zero-gradient Pressurementioning
confidence: 99%
“…The results of the first in-vivo testing of the SV were published in 2021 [50]. Four female sheep were implanted with the SV.…”
Section: Sievers Trileaflet Valvementioning
confidence: 99%